The Influence of Motivation and Work Ability on Employee Productivity at EMP Bentu Ltd - Suryani, Dewi; Ningsih, Dewita Suryani; Junaidi, Rahmat (CV. Strata Persada Academia, 2025)
Employee productivity plays a central role in sustaining organizational competitiveness, particularly in the energy sector where operational efficiency is critical. This study investigates the influence of work motivation and work ability on employee productivity at PT. Energi Mega Persada (EMP) Bentu LTD Pekanbaru. Using a quantitative descriptive approach, data were collected from 80 employees through purposive sampling. Research instruments, measured on a five-point Likert scale, were tested for validity and reliability, with Cronbach’s Alpha values exceeding 0.79, confirming strong internal consistency. Data analysis employed multiple linear regression using SPSS 23 to assess both partial and simultaneous effects. The results demonstrate that both work motivation (β = 0.506, p < 0.001) and work ability (β = 0.331, p = 0.004) significantly and positively affect employee productivity, with motivation identified as the stronger determinant. Descriptive findings further reveal that occupational safety, recognition of achievements, punctuality, and collaboration contribute substantially to productivity outcomes. These findings reinforce human capital theory, emphasizing the dual importance of psychological drivers and technical competence in shaping employee performance. Practically, the study recommends the implementation of structured reward systems, occupational health and safety enhancements, and targeted training programs to optimize workforce potential. Future research should broaden the scope by including gender diversity and organizational culture to provide a more comprehensive understanding of productivity determinants.